Sports facilities in Malaysia : the impacts to urban environments /Dasimah Omar and Maassoumeh Barghchi - Omar, Dasimah; Maassoumeh, Barghchi (Institute of Research, Development and Commercialization, Universiti Teknologi MARA, 2012)
Currently there is tremendous interest in sport in Malaysia, although sport has only been considered as an industry in the last ten years. Sports facilities have improved rapidly, especially after the country hosted the 16th Commonwealth Games in 1998. Internationally, sports facilities are viewed as playing a new role in cities as catalysts for urban development or to regenerate decaying area of the cities. Such a role also provides better justification for public investment, since the provision of sports facilities requires huge amounts of money for construction, ancillary needs and maintenance. The increase in the amount of public money being spent on sports facilities in Malaysia and the proliferation of sports facilities in the country necessitate an investigation into the wider issue of potential benefits related to the development of sports facilities. The aim of this research was to study some existing sports facilities in Malaysia and to examine their impacts on urban environment. The research focused on the main sports facilities at state level in Malaysia. The findings revealed that there is a new trend in sports facilities construction in Malaysia which started in the mid- 1990s. This has been for hosting events, to develop harmony and unite people in line with the Vision 2020 nation-building program and to create a sports culture in the country. The required sports facilities are decided according to urban hierarchies, the National Sports Policy provided by the Ministry of Youth and Sports, and the budget allocation for sports through five-year plans. While the Federal Government provides money for the construction of sports facilities, State and Local Governments each provide land and layout, respectively. The results of the town planners' perceptions survey were able to demonstrate the relationship of sports facilities to the urban environment. It is hoped that the study will provide a new perspective and new approach to realising the potential benefits of sports facilities development in Malaysia. Finally, the research adds more knowledge to the literature on sports facilities development, especially in Malaysia.